Pengaruh Brand Awareness dan Brand Image Terhadap Keputusan Pembelian (Studi Pada Konsumen Shopee di Sumatera Barat) - Fatma Ariani; Rangga Wenda Prinoya (Journal of Technopreneurship on Economics and Business Review, 2021)
Sales and marketing of goods or services using electronic systems will be very developed at this time, which can be seen from the rise of e-commerce platforms that have sprung up, especially in Indonesia. One of them is the Shopee e-commerce platform. This study was conducted to see the effect of the independent variables, namely brand awareness and brand image, on purchasing decisions, which are the dependent variables. The study used multiple linear regression analysis and tested classical assumptions through the SPSS version 21 application. by distributing a questionnaire form online and obtaining as many as 100 answers from various shoppers in West Sumatra. The results of the study partially show that the two variables, namely brand awareness and brand image, have a positive and significant influence on purchasing decisions. Likewise, brand awareness and brand image have a positive and significant influence on purchasing decisions.